Updates in the Management of Paraneoplastic Syndrome - Verma, Neha; Jaffer, Muhammad H.; Kolli, Avinash S.; Mokhtari, Sepideh (Seminars in Neurology, 2024)
Paraneoplastic neurological syndromes (PNS) are defined as remote neurologic immune-mediated effects triggered by underlying systemic tumors. While recognizing specific syndromes can aid early cancer detection, overutilization of paraneoplastic assays in the absence of a classic syndrome can precipitate overdiagnosis and overtreatment. PNS involve autoantibodies targeting intracellular or extracellular antigens, with variable immunotherapy responses based on antigen type. Diagnosing PNS is challenging, requiring exclusion of other differential diagnoses. New diagnostic criteria classify PNS into high-risk and intermediate-risk phenotypes based on clinical phenotype, neuronal antibodies, and cancer presence. Patients with cell surface antibodies respond better to immunotherapies compared to those with intracellular antigen targets. Understanding PNS syndromes, serological markers, and oncological features guides management, which facilitates initiation of immunosuppression for PNS alongside treatment of the underlying neoplasm, thereby improving neurologic and oncologic outcomes. Initial treatments often include intravenous methylprednisolone, plasma exchange, or intravenous immunoglobulins. Second-line immunosuppressants like rituximab or cyclophosphamide may be necessary if initial treatments fail. Specific therapies vary based on antibody target. Here, we summarize the current approach to the investigation, diagnosis, and treatment of patients with suspected PNS.
Keywords: paraneoplastic syndrome; onconeuronal antibodies; autoimmune neurologic syndrome